Implementation of the ‘Kurikulum Merdeka Belajar’ and Its Relationship with Academic Stress Levels and Learning Motivation in Students - Vienlentia, Raisa; Widyanto, I Putu (Indonesian Research Journal on Education, 2025)
Academic stress is prevalent among students, particularly in rigorous and highly competitive academic environments. This stress often arises from the demanding expectations to achieve high performance, excel in assessments, and meet stringent academic standards. The pressure to excel academically, fulfill high expectations, and achieve success in examinations frequently contributes to anxiety, burnout, and a deterioration in students' overall well-being. This research aims to address the question: 'Does the implementation of the 'Kurikulum Merdeka Belajar' provide a more balanced approach to education, thereby reducing the burden and enhancing students' motivation to learn?”. This research uses a quantitative approach with a correlational type of research. Data processing includes editing, coding, scoring and tabulation activities. According to the study's findings, the level of academic stress of Hindu students at SMAN 3 Sampit is 84.6%; the level of motivation of Hindu students at SMAN 3 Sampit is 22.38%; a significance of 0.545 < 0.05 is achieved, indicating that the hypothesis is accepted at the 5% significance level, whereas the alternative hypothesis is rejected, indicating that at the 5% significant level shown from the correlation coefficient figure. As a result, there is no relationship between academic stress and learning motivation of Hindu students at SMAN 3 Sampit during the curriculum transition from K-13 to Kurikulum Merdeka.